Hepatitis C antibody test frequencies and positive rates in Switzerland from 2007 to 2017: a retrospective longitudinal study (Swiss Medical Weekly, 2023)
ACKGROUND AND AIMS: The prevalence of chronic hepatitis C in Switzerland is currently estimated at approximately 32,000 affected individuals (0.37% of the permanent resident population). An estimated 40% of affected individuals in Switzerland is undiagnosed. The Swiss Federal Office of Public Health requires laboratories to report all positive hepatitis C virus (HCV) test results. Approximately 900 newly diagnosed cases are reported annually. The number of HCV tests performed, however, is not collected by the Federal Office of Public Health and positive rates are therefore unknown. The aim of this study was to describe the longitudinal course of the numbers of hepatitis C antibody tests and of positive rates in Switzerland for the years 2007 to 2017.METHODS: Twenty laboratories were asked to provide the number of HCV antibody tests performed and the number of positive antibody tests per year. Using data from the Federal Office of Public Health reporting system for the years 2012 to 2017, we calculated a factor to correct our values for multiple tests of the same person.RESULTS: The annual number of HCV antibody tests performed tripled linearly from 2007 to 2017 (from 42,105 to 121,266) while the number of positive HCV antibody test results increased by only 75% over the same period (from 1360 to 2379). The HCV antibody test positive rate steadily decreased from 3.2% in 2007 to 2.0% in 2017. After correction for multiple tests per person, the person-level HCV antibody tested positive rate decreased from 2.2% to 1.7% from 2012 to 2017.CONCLUSION: In the Swiss laboratories considered, more HCV antibody tests were performed each year in the period (2007–2017) before and during the approval of the new hepatitis C drugs. At the same time, the HCV antibody positive rates decreased, both on a per-test as well as a per-person level. This study is the first to describe the evolution of tests performed and of positive rates for HCV antibody in Switzerland at the national level over several years. In order to more accurately guide future measures to achieve the goal of eliminating hepatitis C by 2030, we recommend annual collection and publication of positive rates by health authorities, along with mandatory reporting of numbers of tests and people treated.